PENGARUH PEMBERIAN DOSISKOMPOS Azolla microphylla TERHADAP BIBIT KAKAO (Theobroma cacao L) DI PEMBIBITAN - Warni, Delta Nervi; Khoiri, M. Amrul; ', Wawan (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This study aims to determine the influences of extending compost dosage of Azolla microphylla for Cocoa seedlings and determine the Azolla microphylla compost dosage which produces growth is the best nursery cocoa seedlings compost. This research was conducted in the experiment stationthe Faculty of Agriculture, University of Riau, Pekanbaru startied from November 2014 through April 2015. The research was conducted experimentally usingcompletely randomized design (CRD). The data were statistically analyzed using analysis of variance, followed by Duncan's New Multiple Range Test (DNMRT) at 5%. Parameters observed were plant height (cm), stem diameter (mm), number of leaves (pieces), leaf area (cmÂ²), seeds dry weight (g) and the ratio of crown roots (g). The results showed that application of Azolla microphylla compost on cocoa seedlings significantly affected stem diameter and has no significant effect against high seedling, number of leaves, leaf area,seed dry weight and root crown ratio, however there was an increasing trend in growth of high seedling, number of leaves, leaf area, the weight of dry seed and root crown ratio without the application of Azolla. microphylla compost. Keywords - cocoa seedlings, Azolla microphylla compost, dose.